2012
DOI: 10.1016/j.epsl.2012.07.041
|View full text |Cite
|
Sign up to set email alerts
|

The Blake geomagnetic excursion recorded in a radiometrically dated speleothem

Abstract: Keywords:geomagnetic excursions speleothems radioisotope geochronology palaeointensity rock magnetism quaternary geochronologyOne of the most important developments in geomagnetism has been the recognition of polarity excursions of the Earth's magnetic field. Accurate timing of the excursions is a key point for understanding the geodynamo process and for magnetostratigraphic correlation. One of the best known excursions is the Blake geomagnetic episode, which occurred during marine isotope stage MIS 5, but its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 36 publications
4
64
0
8
Order By: Relevance
“…This low geomagnetic intensity allowed increased cosmicray fluxes, as evidenced in the deep-sea 10 Be record . This record, and the relative paleointensity record of marine sediments, also indicates short term oscillations in geomagnetic intensity during the Blake excursion Thouveny et al, 2004;Osete et al, 2012). Therefore, the Blake excursion seems a good candidate to test possible links between geomagnetism and paleoclimate.…”
Section: Introductionmentioning
confidence: 64%
“…This low geomagnetic intensity allowed increased cosmicray fluxes, as evidenced in the deep-sea 10 Be record . This record, and the relative paleointensity record of marine sediments, also indicates short term oscillations in geomagnetic intensity during the Blake excursion Thouveny et al, 2004;Osete et al, 2012). Therefore, the Blake excursion seems a good candidate to test possible links between geomagnetism and paleoclimate.…”
Section: Introductionmentioning
confidence: 64%
“…Speleothems may grow continuously for thousands of years, and can be dated with very high accuracy and precision using 230 Th dating, a technique that can be reliably used on specimens younger than 700-600 ka (Edwards et al, 2003;Dorale et al, 2004;Cheng et al, 2013). Recent speleothem magnetism studies have shown that magnetic minerals encapsulated in stalagmites (e.g., Strauss et al, 2013;Font et al, 2014) can be used successfully in dating geomagnetic excursions (Osete et al, 2012), as well as for reconstructing hydrologic and climatic variations (Xie et al, 2013;Bourne et al, 2015). Here we present a speleothem geomagnetic record from Crevice Cave, Missouri, USA (Dorale et al, 1998) that captures the changes in geomagnetic field direction and intensity associated with the Laschamp excursion, dated directly on speleothem calcite using a combination of high-precision 230 Th dating and incremental chronometry from annual growth laminae.…”
Section: Introductionmentioning
confidence: 99%
“…This VDM values is, however, relatively higher than that for geomagnetic excursions during the last 300 kyr determined by the same method (0.6-2.2 Â 10 22 A m 2 , Mochizuki et al, 2006;Yamamoto et al, 2010). Aso-2 deposits were dated at 141 ± 5 ka (Matsumoto et al, 1991), which is not consistent with the established excursion events that are close to the age of Aso-2 formation, namely, the Blake excursion between 116 and 112 ka and the Iceland Basin excursion at about 188 ka (Channell, 2006;Osete et al, 2012). Accordingly, Takai et al (2002) referred to an excursion-like event recorded in Aso-2 deposits as the Aso event.…”
Section: Geological Setting and Samplingmentioning
confidence: 97%